Aspects of defence in Roman Europe - Elton, H; Elton, Hugh (1992)
﻿ This thesis has three parts which can be briefly described as the nature of the threat, the instrument of response and the method of response. Before discussing the military system of the Roman empire, it is necessary to examine its enemies, to see how and why they fought. The first part of the thesis looks at the limitations of the evidence concerning barbarians. It then discusses the social and economic basis of barbarian life, showing their potential for war and the type of threat presented to the Roman empire. The next section deals with the types of conflict between Rome and the barbarians and the reasons for it. There then follows a detailed discussion of barbarian armies and their equipment, strategy and tactics when fighting the Romans. The second section discusses the Roman army. Initially, the organisation of the army is examined, then its troop types and their equipment. This is done with regard to both land and naval forces. Then the sources of soldiers and the problem of barbarization are discussed in some depth. Lastly, the types of fixed defences are briefly examined. Having examined the instrument of response, the third section discusses how it was used. It starts by examining the conditions affecting decision-making at this period, then discusses foreign policy, i.e. whether to use force or alternative methods, with regard to both barbarians and internal enemies. Strategy, i.e. the type of operation employed to defeat the enemy, is then discussed with regard to defence against barbarians, attack against barbarians and against internal enemies. The following part, on operations, discusses how the army performed in the field and analyses tactics for fighting field battles, naval battles and sieges.